Integrasi Nilai Multikultural dalam Pendidikan Islam di Pesantren dalam Membentuk Sikap Toleransi Santri - Rahma Cahyani; Fery Diantoro; Ratri Adelia Sari; Futiya Nafi Husna (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Indonesia as a multicultural country with diverse ethnicities, religions, and cultures requires an educational approach that fosters tolerance and respect for differences. This study aims to analyze the integration of multicultural values in Islamic education within pesantren and its role in shaping students’ tolerant attitudes. The method used in this study is a qualitative approach with a literature study design by analyzing various relevant scientific journals and academic sources. The theoretical framework used in this study is multicultural education theory which emphasizes the importance of recognizing diversity, equality, and the development of inclusive attitudes in the educational process. The results show that the integration of multicultural values in pesantren is carried out comprehensively through formal learning, non-formal activities, and daily social interactions supported by the role of kyai and teachers as role models, which contributes to the formation of students who are tolerant, inclusive, and respectful of diversity.